Data protection in elderly health care platforms - Costa, Ângelo Gonçalo Araújo Silva (2018)
Ambient Assisted Living provides solutions to the increasing cognitive problems that affect the elderly population. To provide all features possible, Ambient Assisted Living projects require access to personal and private information of their users. Currently, the legal issues arisen in Ambient Assisted Living are a hot topic in the European Union, especially aspects regarding unsupervised data processing and cross-sharing of personal information. In this paper it is presented the iGenda project, which is a Cognitive Assistant inserted in the Ambient Assisted Living area which aims to build safe environments that adapt themselves to one’s individual needs. However, one of the issues is the protection of the data flowing within the system and the protection of user’s fundamental rights. It is also presented the principles and legal guarantees of data protection and transmission, and legal aspects are explained, embracing appropriate solutions to technological features that may be a threat.